2016
DOI: 10.1002/aqc.2612
|View full text |Cite
|
Sign up to set email alerts
|

Spatial differences across the French Pyrenees in the use of local habitat by the endangered semi‐aquatic Pyrenean desman (Galemys pyrenaicus)

Abstract: ABSTRACT1. The implementation of effective and appropriate protection actions is frequently hindered by lack of thorough knowledge on species ecology especially in the case of endemic, vulnerable and elusive species.2. Using a recently updated and unpublished dataset describing the spatial distribution of the Pyrenean desman (Galemys pyrenaicus) in its northern range (French Pyrenees), an Ecological Niche Factor Analysis (ENFA) was conducted to provide a quantitative estimate of local habitat use by this endan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 61 publications
0
14
0
3
Order By: Relevance
“…Stream flow velocity has been reported as an important environmental factor for the Pyrenean desman (Charbonnel et al, ). Biffi et al () performed an Ecological Niche Factor Analisys (ENFA) based on the detection of faeces. They concluded that the habitat of the Pyrenean desman is characterized by in‐stream variables (substrate heterogeneity, fast‐flowing water, absence of fine sediment), as well as by bank characteristics (rocky banks), with desmans preferring sites with abundant emergent structures and a high heterogeneity of shelters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stream flow velocity has been reported as an important environmental factor for the Pyrenean desman (Charbonnel et al, ). Biffi et al () performed an Ecological Niche Factor Analisys (ENFA) based on the detection of faeces. They concluded that the habitat of the Pyrenean desman is characterized by in‐stream variables (substrate heterogeneity, fast‐flowing water, absence of fine sediment), as well as by bank characteristics (rocky banks), with desmans preferring sites with abundant emergent structures and a high heterogeneity of shelters.…”
Section: Discussionmentioning
confidence: 99%
“…Desmans usually shelter in natural crevices between rocks, in stone walls, or below the roots of riparian trees; usually there are no outwardly visible signs of the shelters from the surface (Stone, ). They feed mainly on freshwater invertebrates (Biffi et al, ; Santamarina & Guitian, ). Many factors can affect freshwater invertebrate abundance and composition, from pollution to drought, or changes in physical habitat (Cowx, Young, & Hellawell, ; McIntosh, Benbow, & Burky, ; Wood, Agnew, & Petts, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alarming decline of G. pyrenaicus populations over the recent decades across its whole range Gisbert and García-Perea, 2014) has encouraged local, national and European conservation initiatives (e.g., in France: Life+ Desman, 2013;Némoz et al, 2011). Yet, in spite of an increasing number of studies focusing on this species (e.g., Aymerich and Gosàlbez, 2015;Biffi et al, 2016;Charbonnel et al, 2016;Escoda et al, 2017), the respective influence of prey, competitors and predators on its survival and distribution still remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Hasta ese momento, se asumía que el desmán había experimentado regresiones locales y regionales, pero los datos disponibles eran escasos. Poco después se publicaron los resultados de una actualización general de la distribución del desmán en los Pirineos franceses (Biffi et al 2016, que reflejaban también una marcada regresión de la especie en las dos últimas décadas, si bien en Francia hubo algunos cambios metodológicos entre las prospecciones de los años 1980-1990 y las recientes (no se muestrearon tramos idénticos y en la segunda prospección sólo se consideraron positivos los indicios confirmados genéticamente). Estudios recientes llevados a cabo en otras zonas del área de distribución del desmán (por ejemplo Fernández et al 2014Fernández et al , 2017 sugieren igualmente una cierta regresión pero estos datos son poco comparables con los procedentes de los Pirineos, porque las informaciones utilizadas son más heterogéneas.…”
Section: Introductionunclassified